Między determinacją a wyborem w dyskursie telewizyjnym, czyli od TVP Kultura do TVN Style - Loewe, Iwona (Stylistyka, 2019)
The paper describes two TV channels which can be placed on the opposite ends of the scale. On the one hand, there are those dominated by the ethnic culture of the audience; they present linguistic and generic purism. This is the case of TVP Kultura. On the other hand, there are stations which promote freedom of form and language in their communication with the audience and chase diversity on a global scale. This is the case of TVN Style. The broadcast scheduling of TVP Kultura is prevalently a Polish product – 83% of the station’s programs are archival or contemporary Polish productions, 17% are broadcasts purchased from a German-French producer. Polish language programs make up 60% of the TVN Style broadcast scheduling. As the author summarizes, even a Polish language channel reflects the Polish culture. Language, as part of this culture, determines the shape of the broadcasting schedule. Television broadcasters, by addressing their communication to a mass audience, are entangled in its cultural profile. The audience remains united by culture. Thus another determination takes place: the use of a certain model in particular situations, in line with habits of the viewer. TV shows present a great variety of styles, but we would not recognize the style of television in other communicative situations. Currently, the typical traits of television, as pointed out by the author, are repeatability (including self-reference) and the development of a culture of success.